The effectiveness of modified conventional CPR training among North Borneo University Hospital healthcare providers - Ahmad, Nazrin; Wider, Walton; Kadir, Fairrul; Hidrus, Aizuddin; Hassan, Hamidah (Universitas Airlangga, 2023)
Introduction: Numerous studies reported that healthcare providers are not as effective in rendering high-quality CPR over time, despite receiving basic life support (BLS) or advanced cardiac life support (ACLS) training. Thus, to overcome the issue and develop a more feasible implementation of CPR training model, this study aims to identify the effectiveness of a modified conventional training (MT-CPR) method. Method: This was an experimental study conducted to 72 healthcare providers in a teaching hospital in north Borneo. Subjects underwent MT-CPR and data were collected using a validated questionnaire and skills assessment checklist adopted from AHA (2020). Data then was analysed using Friedman, Wilcoxon and McNemar test aided with IBM's Statistical Package for the Social Science (SPSS) statistic software. Result: This study reported that MT-CPR significantly improved the knowledge and skills on CPR (p-value: <0.001). However, the training module significantly incapable to retain the knowledge and skills as early as 3 months post initial MT-CPR (p-value: <0.001). There was a statistically significant difference between the MCQ test scores (pre-course, post-course, and post 3 months-course) with ê“2 (2) = 36.2 (2), p-value = <0.001. There is an association between post-course overall results and post 3 month overall results using McNemar test (p-value < 0.002). Conclusion: Overall, this study indicated that modified CPR training (MT-CPR) were able to develop and improve the CPR knowledge and skill. The adaptation of conventional CPR training method seen effective as it has the capability for better engagement between trainer and participants.